Fast-track Palliation: Evaluating Accelerated Hypofractionated Radiotherapy in Advanced Oral Cavity Cancer - Ramanaiah, Kaluvoya; Varadarajan, Moushmi; Vedagiri, Gautam Vydia; Gandhi, Sadanand Sharosh; Balasundaram, Mukesh; John, Alexander (Asian Pacific Journal of Cancer Care, 2025)
Background: Advanced oral cavity squamous cell carcinoma (OCSCC) in patients with poor performance status presents significant challenges in management, as many are ineligible for curative treatment. Palliative care, particularly radiation therapy, aims to alleviate symptoms and improve quality of life. Accelerated hypofractionated radiotherapy offers a shorter, more intensive treatment course, which may improve patient compliance and provide rapid symptom control. The aim of this study was to evaluate the feasibility, symptom control, toxicity profile, and overall survival of a 5-day course of accelerated hypofractionated palliative radiation therapy in patients with locally advanced OCSCC who are not candidates for curative treatment. Methods: This prospective single-arm pilot study included 8 patients with advanced OCSCC (ECOG performance status 2-3), who were treated with a total dose of 30Gy in 10 fractions of 300cGy twice daily over 5 days. Patients were assessed for symptom control, toxicity, and overall survival (OS) at 1 year. Symptom control was evaluated immediately post-treatment and mucosal/dermal toxicities were monitored at 4 weeks. Results: The median age of patients was 71 years (range 62-80). All patients completed the treatment. Primary symptom control was achieved in 100% of patients, with a reduced need for analgesics post-treatment. Grade 3 mucositis occurred in 5 patients, while 2 experienced Grade 2 mucositis. No Grade 4 toxicities were observed. One patient expired before the 1-month follow-up; 50% of the remaining patients achieved complete remission, and 50% had a partial response. The 1-year overall survival rate was 50%, with a median survival of 16 months (range 1-22 months). Conclusion: Accelerated hypofractionated palliative radiotherapy is a feasible and well-tolerated option for patients with locally advanced OCSCC who are not eligible for the conventional hypofractionated regimens The regimen demonstrated effective symptom control with acceptable toxicity and showed comparable survival outcomes to other palliative radiation regimens. Further studies with larger cohorts are warranted to validate these findings.